Bi2S3-V2CTx heterojunction material, gas sensor as well as preparation method and application of Bi2S3-V2CTx heterojunction material

Through the heterojunction structure of Bi2S3/V2CTx heterojunction material, the lack of performance of traditional gas sensors in NO2 detection is solved, and the rapid response and high sensitivity detection of low concentration NO2 are achieved, and good selectivity and stability are achieved. .

CN119320168APending Publication Date: 2025-01-17SOUTHERN POWER GRID DIGITAL GRID RESEARCH INSTITUTE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411478596.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

When facing low concentration NO2 detection, traditional metal oxide gas sensors have problems such as poor humidity resistance, fluctuations in signal consistency, high operating temperature, large power consumption, and insignificant selectivity. The bismuth sulfide responds to NO2 and is irreversible. , limits its application in gas-sensitive materials.

Method used

Bi2S3/V2CTx heterojunction material is used to form a Schottky heterointerface with Bi2S3 nanorods through hydrothermal reaction, forming a heterojunction structure, improving gas sensitive characteristics, and achieving rapid and sensitive response to low concentrations of NO2. and has gradient and reversibility.

Benefits of technology

It achieves high sensitivity response to NO2 gas, has fast response speed, good selectivity and stability, and is suitable for low concentration NO2 sensing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119320168A_ABST
    Figure CN119320168A_ABST
Patent Text Reader

Abstract

The invention discloses a Bi2S3-V2CTx heterojunction material, a gas sensor as well as a preparation method and application of the gas sensor, and belongs to the technical field of gas sensors. According to the preparation method, the dispersion liquid of the V2CTx nanosheet and the dispersion liquid of the Bi2S3 nanorod are simply mixed, and then hydrothermal reaction is performed to prepare the Bi2S3 / V2CTx heterojunction material, so that the V2CTx with nanosheet morphology and the Bi2S3 with nanorod morphology are promoted to form a Schottky heterogeneous interface, a heterojunction structure is formed, the gas sensitive characteristic of Bi2S3 is improved, rapid sensitive response to low-concentration NO2 can be realized, and the preparation method has the advantages that the preparation method is simple, and the preparation cost is low. The response to NO2 gas has gradient and reversibility, and the selectivity and the stability are relatively good. The Bi2S3 / V2CTx heterojunction material can be prepared without a complex reaction process, and the process is simple.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of gas sensor technology, in particular to Bi2S3-V2CT x Heterojunction materials, gas sensors, and preparation methods and applications thereof. Background Art

[0002] With the rapid development of industry and the increasing number of motor vehicles, nitrogen dioxide (NO2) has become the main source of air pollution. As a toxic gas, NO2 is the main cause of photochemical smog and acid rain. And when the concentration level is greater than 1 ppm, it will cause serious and permanent damage to the human respiratory system. Therefore, highly sensitive and selective sensing of low-concentration NO2 gas is of great significance to human health and environmental protection.

[0003] Traditional metal oxide gas sensors face difficult-to-solve problems such as poor moisture resistance, signal consistency fluctuation deviation, high operating temperature, high power consumption, and unclear selectivity. Two-dimensional metal chalcogenides have high carrier mobility and large specific surface area, which are conducive to electron transfer and gas adsorption. Among them, bismuth sulfide (Bi2S3) has a good band gap, abundant active sites and excellent electrical properties. As a developing functional material, it has received great attention in a variety of applications. However, bismuth sulfide has a low response to nitrogen dioxide and is irreversible, and its application in gas-sensitive materials is still subject to many restrictions. Summary of the invention

[0004] Based on this, it is necessary to provide a Bi2S3 / V2CT x Heterojunction materials, and the Bi2S3 / V2CT x The sensor with heterojunction material as gas-sensitive layer material promotes V2CT with nanosheet morphology through simple mixing and hydrothermal reaction. x It forms a Schottky heterointerface with Bi2S3 with nanorod morphology to constitute a heterojunction structure, which improves the gas sensitive properties of Bi2S3 and can achieve a rapid and sensitive response to low concentrations of NO2. The response to NO2 gas has a gradient and reversibility, and has good selectivity and stability.

[0005] In the first aspect of the present application, there is provided a Bi2S3-V2CT x A method for preparing a heterojunction material comprises the following steps:

[0006] S1: Mix hydrochloric acid and hydrofluoric acid, add V2AlC powder, stir and etch to prepare V2CT x Nanosheets;

[0007] S2: dissolving sodium sulfide nonahydrate and bismuth nitrate in a first solvent respectively, mixing, and performing a first hydrothermal reaction to prepare Bi2S3 nanorods;

[0008] S3: The V2CT x The nanosheets and the Bi2S3 nanorods are dispersed in a second solvent to prepare V2CT x dispersion of nanosheets and dispersion of Bi2S3 nanorods;

[0009] The V2CT x The nanosheet dispersion is mixed with the Bi2S3 nanorod dispersion to prepare a precursor dispersion;

[0010] The precursor dispersion is subjected to a second hydrothermal reaction to prepare the Bi2S3-V2CT x Heterojunction material; in the precursor dispersion, the Bi2S3 nanorods and the V2CT x The mass ratio of the nanosheets is (1-9):1.

[0011] Optional, Bi2S3 nanorods with V2CT x The mass ratio of the nanosheets is (5-9):1; further optionally, the Bi2S3 nanorods and V2CT x The mass ratio of the nanosheets is (7-9):1.

[0012] In some embodiments, the V2CT x In the dispersion of nanosheets, V2CT x The mass concentration of the nanosheets is 1 to 20 mg / mL; in the dispersion of the Bi2S3 nanorods, the mass concentration of the Bi2S3 nanorods is 1 to 20 mg / mL.

[0013] In some embodiments, the Bi2S3 nanorods have an average diameter of 60-100 nm and a length of 500-800 nm; the V2CT x The average size of the nanosheets is 2~3μm.

[0014] In some embodiments, the first solvent is selected from at least one of deionized water, ethylene glycol, and ethanol; and the second solvent is selected from at least one of deionized water, methanol, and ethanol.

[0015] In some embodiments, the volume ratio of the hydrofluoric acid to the hydrochloric acid is (1-3):1, and the ratio of the total amount of the hydrofluoric acid and the hydrochloric acid to the V2AlC is (10-40) mL:1 g; the stirring etching conditions are stirring at 30-40°C for 12-36 hours, and then stirring at 45-55°C for 36-60 hours.

[0016] In some embodiments, the molar ratio of the sodium sulfide nonahydrate to the bismuth nitrate is 2:(0.5-1.5).

[0017] In some embodiments, the conditions of the first hydrothermal reaction and the second hydrothermal reaction are independently: reacting at 100-200° C. for 10-30 hours.

[0018] The second aspect of the present application provides Bi2S3-V2CT prepared by the above preparation method x Heterojunction materials.

[0019] In some embodiments, the Bi2S3 nanorods and the V2CT x The nanosheets form a heterojunction structure.

[0020] In a third aspect of the present application, a gas sensor is provided, comprising a gas-sensitive layer, wherein the gas-sensitive layer comprises a gas-sensitive material, wherein the gas-sensitive material comprises Bi2S3-V2CT prepared by the preparation method described in the first aspect. x Heterojunction material or Bi2S3 / V2CT described in the second aspect x Heterojunction materials.

[0021] In some embodiments, the gas sensor further comprises a substrate and interdigital electrodes, wherein the interdigital electrodes are disposed on at least one side of the substrate, and the gas sensitive layer is disposed on a surface of the interdigital electrodes away from the substrate.

[0022] In some embodiments, the substrate is selected from one or more of silicon, polymer, ceramic, and sapphire substrates.

[0023] In some embodiments, the distance between the positive and negative electrodes of the interdigitated electrodes is 200-900 μm.

[0024] In some embodiments, the number of the interdigital electrodes is one or more. When the number of the interdigital electrodes is plural, the distance between two adjacent interdigital electrodes is 50-500 μm.

[0025] In a fourth aspect of the present application, a method for preparing a gas sensor is provided, comprising the following steps:

[0026] Step 1, providing interdigital electrodes on a substrate;

[0027] Step 2: Prepare the gas-sensitive material into a gas-sensitive layer dispersion, apply it onto the surface of the interdigital electrode away from the substrate, dry it to form a gas-sensitive layer, and prepare the gas sensor.

[0028] In a fifth aspect of the present application, a gas sensing device is provided, comprising the gas sensor described in the third aspect or the gas sensor prepared by the preparation method described in the fourth aspect.

[0029] In the sixth aspect of the present application, there is provided Bi2S3-V2CT prepared by the preparation method described in the first aspect. x Heterojunction material, Bi2S3 / V2CT described in the second aspect x Application of the heterojunction material, the gas sensor described in the third aspect, the gas sensor prepared by the preparation method described in the fourth aspect, and the gas sensing device described in the fifth aspect in nitrogen dioxide sensing.

[0030] Bi2S3 / V2CT prepared by the preparation method provided in this application x Bi2S3 in heterojunction materials has nanorod morphology, V2CT x It has a nanosheet morphology and good gas sensitivity, and can be well applied to NO2 and other gas sensing. In addition, this application adopts V2CT x The dispersion of nanosheets and the dispersion of Bi2S3 nanorods were simply mixed and then subjected to hydrothermal reaction to prepare Bi2S3 / V2CT. x Heterojunction materials can be prepared without complicated reaction processes to obtain Bi2S3 / V2CT x Heterojunction material, simple process.

[0031] A gas sensor provided in the present application can achieve a high-sensitivity response to NO2 with a fast response speed. In addition, it can realize the sensing of low-concentration NO2.

[0032] A preparation method of a gas sensor provided in the present application adopts a micromachining method to prepare interdigital electrodes on a substrate, and then covers the surface with a layer of nano-heterojunction material as a gas-sensitive coating to obtain a gas sensor. The method is simple, has high preparation accuracy, and the obtained gas sensor has stable quality.

[0033] A gas sensor device provided in the present application can achieve a high-sensitivity response to NO2 gas, with a short response time, and good selectivity and stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] In order to more clearly illustrate the technical solutions in the embodiments of the present application or the prior art, the following briefly introduces the drawings required for use in the embodiments or the prior art description. The drawings are only used to illustrate the preferred implementation methods and are not considered to be limitations of the present application. The same reference symbols are used throughout the drawings to represent the same components. In the drawings:

[0035] Figure 1Schematic diagram of the synthesis of this application, (a) Bi2S3 / V2CT x Preparation of heterojunction materials; (b) Bi2S3 / V2CT x Schematic diagram of the synthesis of gas sensing devices.

[0036] Figure 2 The Bi2S3 nanorods and V2CT of Example 4 x Nanosheets and Bi2S3 / V2CT x Structural characterization of heterojunction materials, (a) SEM image of Bi2S3 nanorods; (b) V2CT x SEM image of nanosheets; (c) Bi2S3 / V2CT x SEM image of heterojunction materials; (d) TEM image of Bi2S3 nanorods; (e) Bi2S3 / V2CT x TEM image of heterojunction materials; (f) Bi2S3 / V2CT x HRTEM image of heterojunction material.

[0037] Figure 3 The Bi2S3 nanorods, V2AlC powder, and V2CT of Example 4 x Nanosheets and Bi2S3 / V2CT x XRD patterns of heterojunction materials.

[0038] Figure 4 The Bi2S3 nanorods and V2CT of Example 4 x Nanosheets and Bi2S3 / V2CT x Full XPS spectrum of heterojunction material.

[0039] Figure 5 The response curves of the gas sensors of Example 4 and Comparative Example 1 to 20 ppm NO2 at room temperature are as follows: (a) Response curve of the gas sensor of Comparative Example 1 to 20 ppm NO2 at room temperature; (b) Response curve of the gas sensor of Example 4 to 20 ppm NO2 at room temperature; the rectangular area with gray frame lines represents the sensor being in 20 ppm NO2 with dry air as background gas, and the 365 nm ultraviolet light irradiation is turned on while the introduction of NO2 is stopped, and the remaining white areas represent the sensor being in dry air atmosphere.

[0040] Figure 6The gas-sensitive test performance diagrams of the gas sensor of Example 4 include: (a) cyclic stability curve of 20 ppm NO2 at room temperature; (b) gradient curve of response to 1-40 ppm NO2 at room temperature; (c) long-term stability curve of 20 ppm NO2; (d) selectivity test diagram of 20 ppm NO2, NH3, H2, CO, CH4 and C2H5OH. DETAILED DESCRIPTION

[0041] In order to make the purpose, technical solution and advantages of this application clearer and to provide a more thorough and comprehensive understanding of the disclosed content of this application, the technical solution of this application will be clearly and completely described below in conjunction with the specific embodiments of this application and the corresponding drawings. The described embodiments are only part of the embodiments of this application, not all of them.

[0042] The implementation of the present application is described in detail below in conjunction with the accompanying drawings. This embodiment is implemented based on the technical solution of the present application, and a detailed implementation method and specific operation process are given, but the protection scope of the present application is not limited to the following embodiments.

[0043] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.

[0044] the term

[0045] Unless otherwise specified or incompatible herewith, the terms and phrases used herein shall have the following meanings:

[0046] In the present application, "plurality", "multiple" and the like, unless otherwise specified, refer to a number greater than or equal to 2. For example, "one or more" or "at least one" means one or greater than or equal to two.

[0047] In the present application, the terms "further", "particularly" and the like are used for descriptive purposes to indicate differences in content, but should not be construed as limiting the scope of protection of the present application.

[0048] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0049] In the present application, when it comes to a numerical interval (i.e., a numerical range), unless otherwise specified, the distribution of the optional numerical values ​​in the numerical interval is considered to be continuous, and includes the two numerical endpoints (i.e., the minimum value and the maximum value) of the numerical interval, and each numerical value between the two numerical endpoints. Unless otherwise specified, when the numerical interval only refers to the integers in the numerical interval, it includes the two endpoint integers of the numerical range, and each integer between the two endpoints, which is equivalent to directly listing each integer. When multiple numerical ranges are provided to describe features or characteristics, these numerical ranges can be combined. In other words, unless otherwise specified, the numerical range disclosed herein should be understood to include any and all sub-ranges included therein. The "numerical value" in the numerical interval can be any quantitative value, such as a number, a percentage, a ratio, etc. "Numerical interval" allows broadly including numerical interval types such as percentage intervals, ratio intervals, and ratio intervals.

[0050] In the present application, the term "room temperature" generally refers to 4-35° C., preferably 20±5° C. In the embodiments of the present application, room temperature refers to 20-30° C.

[0051] In this application, unless otherwise specified, the temperature parameter is allowed to be either a constant temperature treatment or to vary within a certain temperature range. It should be understood that the constant temperature treatment allows the temperature to fluctuate within the accuracy range controlled by the instrument. Fluctuations within the range of ±5°C, ±4°C, ±3°C, ±2°C and ±1°C are allowed.

[0052] In this application, when referring to the unit of a data range, if there is a unit only after the right endpoint, it means that the units of the left and right endpoints are the same. For example, 2~5h means that the units of the left endpoint "2" and the right endpoint "5" are both h (hours).

[0053] In the first aspect of the present application, there is provided a Bi2S3-V2CT x A method for preparing a heterojunction material comprises the following steps:

[0054] S1: Mix hydrochloric acid and hydrofluoric acid, add V2AlC powder, stir and etch to prepare V2CT x Nanosheets;

[0055] S2: dissolving sodium sulfide nonahydrate and bismuth nitrate in the first solvent respectively, mixing, and performing a hydrothermal reaction to prepare Bi2S3 nanorods;

[0056] S3: The V2CT x The nanosheets and the Bi2S3 nanorods are dispersed in a second solvent to prepare V2CT x dispersion of nanosheets and dispersion of Bi2S3 nanorods;

[0057] The V2CTx The nanosheet dispersion is mixed with the Bi2S3 nanorod dispersion to prepare a precursor dispersion;

[0058] The precursor dispersion is subjected to a hydrothermal reaction to prepare the Bi2S3-V2CT x Heterojunction material; in the precursor dispersion, the Bi2S3 nanorods and the V2CT x The mass ratio of the nanosheets is (1-9):1.

[0059] As a gas-sensitive material, Bi2S3 nanorods are not very responsive to low concentrations of NO2 and are irreversible. As a new type of transition metal carbon / nitride two-dimensional nanolayered material, MXene has attracted extensive attention from the academic community in recent years in many fields such as sensors, energy storage and conversion, and multifunctional polymer heterojunction materials due to its unique physical and chemical properties. MXene has excellent electrical conductivity and can be used as a sensing material. Vanadium carbide (V2CT x ) is a MXene material. Two-dimensional V2CT synthesized by selectively etching the metallic Al atoms of the V2AlC powder phase structure x The rich functional groups on its surface provide reactive sites, which are very helpful in improving the sensitivity of gas sensors.

[0060] However, the experiment found that V2CT x The nanosheets also have a low response to low concentrations of NO2. x The dispersion of nanosheets and Bi2S3 nanorods was simply mixed and then subjected to hydrothermal reaction to find that V2CT with nanosheet morphology x It can form a Schottky heterojunction interface with Bi2S3 with nanorod morphology to form a heterojunction structure. x Compared with Bi2S3, heterojunction materials have improved gas-sensitive properties and can achieve rapid and sensitive response to low-concentration NO2. The response to NO2 gas has a gradient and reversibility, and has good selectivity and stability.

[0061] In addition, this application adopts V2CT x The dispersion of nanosheets and the dispersion of Bi2S3 nanorods were simply mixed and then subjected to hydrothermal reaction to prepare Bi2S3 / V2CT. x Heterojunction materials can be prepared without complicated reaction processes to obtain Bi2S3 / V2CT x Heterojunction material, simple process.

[0062] It should be noted that there is no special requirement for the concentration of hydrofluoric acid and hydrochloric acid, and common commercially available specifications can be selected. For example, hydrofluoric acid can be 40wt% HF, 48wt% HF, etc., and hydrochloric acid can be 12M HCl, etc.

[0063] Optional, Bi2S3 nanorods with V2CT x The mass ratio of the nanosheets is (5-9):1; further optionally, the Bi2S3 nanorods and V2CT x The mass ratio of the nanosheets is (7-9):1.

[0064] It is understandable that Bi2S3 nanorods and V2CT x The mass ratio of the nanosheets can be adjusted in combination with the gas sensitivity, and specifically can be 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, etc.

[0065] In some embodiments, the V2CT x In the dispersion of nanosheets, V2CT x The mass concentration of the nanosheets is 1 to 20 mg / mL, for example, it can be 1 mg / mL, 2 mg / mL, 3 mg / mL, 4 mg / mL, 5 mg / mL, 6 mg / mL, 7 mg / mL, 8 mg / mL, 9 mg / mL, 10 mg / mL, 11 mg / mL, 12 mg / mL, 13 mg / mL, 14 mg / mL, 15 mg / mL, 16 mg / mL, 17 mg / mL, 18 mg / mL, 19 mg / mL, 20 mg / mL and the like.

[0066] In some embodiments, the mass concentration of the Bi2S3 nanorods in the dispersion of the Bi2S3 nanorods is 1 to 20 mg / mL, for example, 1 mg / mL, 2 mg / mL, 3 mg / mL, 4 mg / mL, 5 mg / mL, 6 mg / mL, 7 mg / mL, 8 mg / mL, 9 mg / mL, 10 mg / mL, 11 mg / mL, 12 mg / mL, 13 mg / mL, 14 mg / mL, 15 mg / mL, 16 mg / mL, 17 mg / mL, 18 mg / mL, 19 mg / mL, 20 mg / mL, etc.

[0067] It should be noted that by adjusting V2CT x The concentration and ratio of the dispersion of nanosheets and the dispersion of Bi2S3 nanorods can achieve the Bi2S3 nanorods and V2CT in the precursor dispersion. x Adjustment of the mass ratio of nanosheets.

[0068] In some embodiments, the Bi2S3 nanorods have an average diameter of 60-100 nm and a length of 500-800 nm; the V2CT x The average size of the nanosheets is 2-3 μm; for example, the average diameter of the Bi2S3 nanorods may be 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, etc.; the length of the Bi2S3 nanorods may be 500 nm, 600 nm, 700 nm, 800 nm, etc.; the V2CT x The average size of the nanosheets may be 2 μm, 2.1 μm, 2.2 μm, 2.3 μm, 2.4 μm, 2.5 μm, 2.6 μm, 2.7 μm, 2.8 μm, 2.9 μm, 3.0 μm, etc.

[0069] In some embodiments, the first solvent is selected from at least one of deionized water, ethylene glycol and ethanol; the second solvent is selected from at least one of deionized water, methanol and ethanol. It is understood that the first solvent and the second solvent can be a single solvent or a combination of two or more solvents.

[0070] In some embodiments, the volume ratio of the hydrofluoric acid to the hydrochloric acid is (1-3):1, and the total amount of the hydrofluoric acid and the hydrochloric acid to the V2AlC is (10-40) mL:1 g; the stirring etching condition is stirring at 30-40° C. for 12-36 h, and then stirring at 45-55° C. for 36-60 h; for example, the volume ratio of the hydrofluoric acid to the hydrochloric acid can be 1:1, 1.5:1, 2:1, 2.5:1, 3:1, etc., and the hydrofluoric acid and the hydrochloric acid are mixed at a ratio of (10-40) mL:1 g. The ratio of the total amount of acid to the V2AlC is 10mL:1g, 20mL:1g, 30mL:1g, 40mL:1g, etc.; the stirring etching conditions can be stirring at 30, 31, 32, 33, 34, 35, 36, 37, 38, 39 or 40°C for 12, 18, 24, 30, 36h, and then stirring at 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55°C for 36, 42, 48, 54, 60h, etc.

[0071] In some embodiments, the molar ratio of the sodium sulfide nonahydrate to the bismuth nitrate is 2:(0.5-1.5), for example, it can be 2:0.5, 2:1, 2:1.5, etc.

[0072] It should be noted that the V2CT xIn the preparation process of the dispersion of nanosheets, an ultrasonic step may be included after dispersion. Any common ultrasonic equipment may be used, such as a cell disruptor, an ultrasonic instrument, etc. When a cell disruptor is used, the power of the cell disruptor may be 100 to 400 W; and the ultrasonic time may be 1 to 2 h. Other mixing steps may also include an ultrasonic step. It is understood that ultrasound is beneficial to improving the dispersion or mixing effect.

[0073] It should be noted that the molar volume ratio of sodium sulfide nonahydrate to the first solvent is (1-10) mmol:15 mL, for example, 2 mmol:15 mL; the molar volume ratio of bismuth nitrate to the first solvent is (0.5-5) mmol:15 mL, for example, 1 mmol:15 mL.

[0074] It should be noted that the V2CT x In the step of mixing the dispersion of nanosheets and the dispersion of Bi2S3 nanorods, V2CT x The dispersion of nanosheets and the dispersion of Bi2S3 nanorods are mixed; for example, V2CT x The dispersion of nanosheets is added to the dispersion of Bi2S3 nanorods; the stirring speed can be 100 to 500 rpm, and the stirring time can be 1 to 2 h.

[0075] It should be noted that the stirring etching may also include washing and drying steps; the drying method includes freeze drying; the drying temperature may be -60 to -40°C; and the drying time may be 10 to 30 hours. The first hydrothermal reaction may also include washing and drying steps; the drying method includes vacuum drying; the drying temperature may be 50-80°C; and the drying time may be 10-30 hours. The second hydrothermal reaction may also include washing and drying steps; the drying method includes vacuum drying; the drying temperature is 40 to 80°C; and the drying time is 8 to 15 hours; the solvent used for washing is selected from at least one of deionized water and ethanol.

[0076] It is understandable that the above drying method and washing conditions are not particularly limited, and common drying methods (such as heating drying, vacuum drying, freeze drying, natural drying, etc.) and common washing methods can be used. The above are only examples of drying and washing. In addition, before washing, a solid-liquid separation step can be included, and a common solid-liquid separation method (centrifugation, filtration, etc.) can be used. For example, centrifugation can be used, and the centrifugal speed can be 4000-8000 rpm, and the centrifugal time can be 5-30 min;

[0077] In some embodiments, the conditions of the first hydrothermal reaction and the second hydrothermal reaction are independently: reaction at 100-200°C for 10-30 hours, for example, reaction at 100, 120, 140, 160, 180, 200°C for 10, 12, 15, 18, 21, 24, 27, 30 hours, etc.

[0078] The second aspect of the present application provides Bi2S3-V2CT prepared by the above preparation method x Heterojunction materials.

[0079] In some embodiments, the Bi2S3 nanorods and the V2CT x The nanosheets form a heterojunction structure.

[0080] In a third aspect of the present application, a gas sensor is provided, comprising a gas-sensitive layer, wherein the gas-sensitive layer comprises a gas-sensitive material, wherein the gas-sensitive material comprises Bi2S3-V2CT prepared by the preparation method described in the first aspect. x Heterojunction material or Bi2S3 / V2CT described in the second aspect x Heterojunction materials.

[0081] It can be understood that the Bi2S3 nanorods and the V2CT x The nanosheets form a heterojunction structure.

[0082] The Bi2S3 / V2CT provided in this application x Heterojunction materials have good gas-sensitive properties and can be well applied to the sensing of gases such as NO2. The prepared gas sensors can achieve high-sensitivity response to NO2 and a fast response speed. In addition, they can also sense low-concentration NO2.

[0083] In some embodiments, the gas sensor further comprises a substrate and interdigital electrodes, wherein the interdigital electrodes are disposed on at least one side of the substrate, and the gas sensitive layer is disposed on a surface of the interdigital electrodes away from the substrate.

[0084] In some embodiments, the substrate is selected from one or more of silicon, polymer, ceramic, and sapphire substrates.

[0085] In some embodiments, the distance between the positive and negative electrodes of the interdigitated electrodes is 200-900 μm.

[0086] In some embodiments, the number of the interdigital electrodes is one or more. When the number of the interdigital electrodes is plural, the distance between two adjacent interdigital electrodes is 50-500 μm.

[0087] In a fourth aspect of the present application, a method for preparing a gas sensor is provided, comprising the following steps:

[0088] Step 1, providing interdigital electrodes on a substrate;

[0089] Step 2: Prepare the gas-sensitive material into a gas-sensitive layer dispersion, apply it onto the surface of the interdigital electrode away from the substrate, dry it to form a gas-sensitive layer, and prepare the gas sensor.

[0090] It should be noted that the solvent of the gas-sensitive layer dispersion can be water. In the gas-sensitive layer dispersion, the mass concentration of the gas-sensitive material can be 1~20 mg / mL, for example, it can be 1 mg / mL, 2 mg / mL, 3 mg / mL, 4 mg / mL, 5 mg / mL, 6 mg / mL, 7 mg / mL, 8 mg / mL, 9 mg / mL, 10 mg / mL, 11 mg / mL, 12 mg / mL, 13 mg / mL, 14 mg / mL, 15 mg / mL, 16 mg / mL, 17 mg / mL, 18 mg / mL, 19 mg / mL, 20 mg / mL, etc.

[0091] The coating amount of the gas-sensitive layer dispersion is based on the thickness of the usual gas-sensitive layer, for example, it can be 2-10μm, specifically 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, etc.

[0092] It can be understood that the present application adopts micromachining method to process and prepare interdigital electrodes on a substrate, and then covers the surface with a layer of nano-heterojunction material as a gas-sensitive coating to prepare a gas sensor. The method is simple, has high preparation accuracy, and the obtained gas sensor has stable quality.

[0093] In a fifth aspect of the present application, a gas sensing device is provided, comprising the gas sensor described in the third aspect or the gas sensor prepared by the preparation method described in the fourth aspect.

[0094] It is understandable that the gas sensing device may be a sensing device or a detection device based on the gas sensor, which may include devices other than the gas sensor.

[0095] In the sixth aspect of the present application, there is provided Bi2S3-V2CT prepared by the preparation method described in the first aspect. x Heterojunction material, Bi2S3 / V2CT described in the second aspect x Application of the heterojunction material, the gas sensor described in the third aspect, the gas sensor prepared by the preparation method described in the fourth aspect, and the gas sensing device described in the fifth aspect in nitrogen dioxide sensing.

[0096] It is understandable that the gas sensor device of the present application can achieve a high-sensitivity response to NO2 gas, a short response time, and good selectivity and stability.

[0097] In order to make it easier to understand and implement the present application, the following easier-to-implement, more specific and detailed embodiments and comparative examples are provided as references.

[0098] At an operating voltage of 500 mV, an Agilent 4156C semiconductor parameter analyzer is used to record the real-time current changes of the gas sensor. The gas response of the sensor is defined as S = |R g -R a | / R a , where R a is the resistance in dry air environment, R g is the resistance of the sensor when exposed to the target gas. The response and recovery times (τres and τrec) are defined as the time it takes for the sensor signal to reach 90% of the total resistance change after gas injection and release.

[0099] Unless otherwise specified, the raw materials used in the following experiments can be purchased from the market.

[0100] The following are specific embodiments.

[0101] Example 1

[0102] Figure 1 Schematic diagram of the synthesis of this application, (a) Bi2S3 / V2CT x Preparation of heterojunction materials; (b) Bi2S3 / V2CT x Schematic diagram of the synthesis of gas sensor devices. The specific preparation process is as follows:

[0103] 1. Bi2S3 / V2CT x Preparation of heterojunction materials:

[0104] S1: 12 mL of hydrofluoric acid (48wt% HF) and 8 mL of hydrochloric acid (12M HCl) were mixed, and then 1.0 g of V2AlC powder was slowly added within 5 min. The mixture was stirred at a water bath temperature of 35°C for 24 h, and then at a water bath temperature of 50°C for 48 h. The obtained product was then washed with deionized water to remove residual metal salts. The suspension was then repeatedly centrifuged and washed until the pH of the supernatant was 6. The precipitate was collected and freeze-dried to obtain V2CT. x Nanosheets;

[0105] S2: Dissolve 1 mmol bismuth nitrate and 2 mmol sodium sulfide nonahydrate in 15 mL ethylene glycol to prepare bismuth nitrate solution and bismuth nitrate solution, add sodium sulfide nonahydrate solution dropwise to the bismuth nitrate solution while stirring, and stir thoroughly for 1 h. Then, heat at 180℃ for 24 h. After cooling, wash the black precipitate alternately with deionized water and ethanol, collect and dry at 60℃ for 12 h to obtain bismuth sulfide nanorods;

[0106] S3: V2CT x Dispersed in water, the cells were ultrasonically treated in an ice bath using a cell disruptor (power 200 W, time 1 h) to prepare V2CT. x Nanosheet dispersion (V2CT x The mass concentration of the nanosheets is 1 mg / mL); dispersing the Bi2S3 nanorods in water to prepare a dispersion of Bi2S3 nanorods (the mass concentration of the Bi2S3 nanorods is 1 mg / mL);

[0107] According to V2CT x The mass ratio of nanosheets to Bi2S3 nanorods is 1:1. x The dispersion of nanosheets was added dropwise to the dispersion of Bi2S3 nanorods and stirred for 30 min to prepare a precursor dispersion.

[0108] The precursor dispersion was placed in a 180℃ hydrothermal bath for 12 h. After cooling, the final black precipitate was washed with deionized water, dried at 60℃ under vacuum for 8 h, and the dried precipitate powder was annealed at 300℃ under N2 atmosphere for 3 h to obtain Bi2S3 / V2CT x Heterojunction materials.

[0109] 2. Preparation of gas sensor

[0110] The gold electrodes were prepared by micromachining technology, and the distance between the positive and negative electrodes was controlled to be 800 μm, and the distance between adjacent electrodes was 300 μm. x Dispersion (solvent is water, Bi2S3 / V2CT x In the dispersion, Bi2S3 / V2CT x The mass concentration of the heterojunction material is 5 mg / mL) and then dropped onto the electrode surface and dried in vacuum at 60 °C for 1 h to form a gas-sensitive layer (Bi2S3 / V2CT x The average thickness of the gas-sensitive layer composed of heterojunction materials is about 6 μm), thus obtaining Bi2S3 / V2CT x Gas sensor, the sensor is denoted as BSVC-1.

[0111] Embodiments 2 to 6

[0112] Preparation of Bi2S3 / V2CT in Examples 2 to 6 x The method of heterojunction material is basically the same as that in Example 1, except that in the precursor dispersion, Bi2S3 nanorods and V2CT x The mass ratios of the nanosheets are 3:1, 5:1, 7:1 and 9:1, respectively.

[0113] Prepared Bi2S3 / V2CT x After the heterojunction materials were prepared, gas sensors were constructed using the same method as in Example 1. The prepared gas sensors were named BSVC-3, BSVC-5, BSVC-7 and BSVC-9, respectively.

[0114] Comparative Example 1

[0115] The Bi2S3 nanorods in Example 4 were used as gas-sensitive materials, and a gas sensor was constructed using the same method as in Example 1. The prepared gas sensor was denoted as Bi2S3.

[0116] Comparative Example 2

[0117] Using V2CT in Example 4 x The nanosheets were used as gas-sensitive materials, and a gas sensor was constructed using the same method as in Example 1. The prepared gas sensor was denoted as V2C.

[0118] Test Case

[0119] 1. Bi2S3 / V2CT of Example 4 x Heterojunction materials, Bi2S3 nanorods and V2CT x Structural characterization of nanosheets.

[0120] Figure 2 The Bi2S3 nanorods and V2CT of Example 4 of the present application x Nanosheets and Bi2S3 / V2CT x Structural characterization diagram of heterojunction materials, where (a) is the SEM image of Bi2S3 nanorods, and (d) is the TEM image of Bi2S3 nanorods. It can be seen that the Bi2S3 nanorods are uniform in size, with an average size of about 600-800 nm; (b) is the V2CT x SEM image of the nanosheet shows V2CT x The nanosheets are multilayer nanosheets with a size greater than 2 μm and an accordion-like structure; (c) is Bi2S3 / V2CT x SEM image of heterojunction material shows that Bi2S3 nanorods are evenly and tightly compounded in V2CT x On nanosheets; (e) is Bi2S3 / V2CT x TEM image of heterojunction material shows that Bi2S3 nanorods are uniformly composited in V2CT x Between nanosheet layers or on the surface; (f) is Bi2S3 / V2CT x HRTEM image of heterojunction material, Bi2S3 nanorods and V2CT can be clearly seen x The different orientations of the nanosheets' crystal faces demonstrate the successful composite of the two materials.

[0121] Figure 3 The Bi2S3 nanorods, V2AlC powder, and V2CT of Example 4 of the present application x Nanosheets and Bi2S3 / V2CT x XRD diagram of heterojunction material, which also contains the XRD diagram of standard Bi2S3 card. It can be seen that V2CT x The successful etching of the Bi2S3 nanorods prepared by the technical solution of this application matches the standard card of Bi2S3 (JCPDS No. #17-0320), Bi2S3 / V2CT x The XRD match between the heterojunction material and the Bi2S3 nanorods indicates that Bi2S3 / V2CT was successfully synthesized while maintaining the microstructure of pure bismuth sulfide. x Material.

[0122] Figure 4 The Bi2S3 nanorods and V2CT of Example 4 of the present application x Nanosheets and Bi2S3 / V2CT x The full XPS spectrum of heterojunction materials shows that Bi2S3 nanorods and V2CT x Nanosheets and Bi2S3 / V2CT x Heterojunction materials.

[0123] 2. The gas sensing performance of Examples 1-6 and Comparative Examples 1-2 was tested. The results are shown in Tables 1-2 and Figure 5-6 In this application, unless otherwise specified, response test refers to testing the change in the resistance value Rg of the sensor in the test atmosphere and the resistance value Ra in dry air, with |Rg-Ra| / Ra×100% as the response value of the sensor; response time refers to the time taken for the resistance value of the sensor to change to 90% of |Rg-Ra|, calculated from the time when the atmosphere in which the sensor is located changes from the dry air atmosphere to the test atmosphere.

[0124] Figure 5The following are the response curves of the gas sensors of Example 4 (BSVC-7) and Comparative Example 1 to 20 ppm NO2 at room temperature: (a) The response curve of the gas sensor of Comparative Example 1 to 20 ppm NO2 at room temperature; (b) The response curve of the gas sensor of Example 4 to 20 ppm NO2 at room temperature; the rectangular area with gray frame lines is the sensor in 20 ppm NO2 with dry air atmosphere as the background gas, and the 365 nm ultraviolet light irradiation is turned on while the NO2 is stopped, and the remaining white area is the sensor in dry air atmosphere. It can be seen that the Bi2S3 nanorods have an incomplete recovery of the response to 20 ppm NO2, while the response of BSVC-7 to 20 ppm NO2 can be fully recovered, with a response value of 190.57% and a response time of 20 s; the specific response values ​​can also be seen in Table 2.

[0125] Figure 6 The gas-sensitive test performance diagram of the gas sensor (BSVC-7) of Example 4 of the present application, (a) and (b) are the cyclic stability curve of the gas sensor (BSVC-7) to 20 ppm NO2 at room temperature and the gradient concentration response curve to 1-40 ppm NO2. It can be seen that in five consecutive cycles, the response sensitivity and recovery of the sensor to NO2 maintain good stability, and the response to 1-40 ppm NO2 gas has gradient and reversibility; (c) is the long-term stability diagram of the sensor BSVC-7 in Example 4 in response to 20 ppm NO2 at room temperature. The stability test of the sensor was carried out within four weeks. It can be seen that the long-term stability is maintained well, and the sensing performance is still more than 90% after four weeks; (d) is the selectivity test diagram of the sensor BSVC-7 in Example 4 to 20 ppm NO2, NH3, H2, CO, CH4 and C2H5OH. It can be seen that the sensor has very small responses to NH3, H2, CO, CH4 and C2H5OH gases; the specific response values ​​can also be found in Table 1.

[0126] Table 1. Gas sensor BSVC-7 in Example 4

[0127] Response to 20 ppm NO2, NH3, H2, CO, CH4 and C2H5OH at room temperature

[0128]

[0129] Table 2. Response values ​​of the gas sensors in Examples 1 to 6 and Comparative Example 1 to 20 ppm NO2 at room temperature

[0130]

[0131] In summary, the use of Bi2S3 nanorods or V2CT alone x Nanosheets are used as gas-sensitive materials to prepare gas sensors, which have a low response to low concentrations of NO2. x Modification of Bi2S3 nanorods by nanosheets can improve the gas-sensing properties of Bi2S3 nanorods, achieve high-sensitivity response to NO2 gas, short response time, gradient and reversibility of response to NO2 gas, and good selectivity and stability.

[0132] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0133] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent of the present application shall be subject to the attached claims.

Claims

1. A Bi2S3-V2CT x A method for preparing a heterojunction material, characterized in that: The steps include: Mix hydrochloric acid and hydrofluoric acid, add V2AlC powder, stir and etch to prepare V2CT x Nanosheets; Dissolving sodium sulfide nonahydrate and bismuth nitrate in a first solvent respectively, mixing, and performing a first hydrothermal reaction to prepare Bi2S3 nanorods; The V2CT x The nanosheets and the Bi2S3 nanorods are dispersed in a second solvent to prepare V2CT x dispersion of nanosheets and dispersion of Bi2S3 nanorods; The V2CT x The nanosheet dispersion is mixed with the Bi2S3 nanorod dispersion to prepare a precursor dispersion; The precursor dispersion is subjected to a second hydrothermal reaction to prepare the Bi2S3-V2CT x Heterojunction material; in the precursor dispersion, the Bi2S3 nanorods and the V2CT x The mass ratio of the nanosheets is (1-9):1; Optionally, the Bi2S3 nanorods and the V2CT x The mass ratio of nanosheets is (5-9):1; Further optionally, the Bi2S3 nanorods and the V2CT x The mass ratio of the nanosheets is (7-9):

1.

2. The preparation method according to claim 1, characterized in that The V2CT x In the dispersion of nanosheets, V2CT x The mass concentration of the nanosheets is 1 to 20 mg / mL; in the dispersion of the Bi2S3 nanorods, the mass concentration of the Bi2S3 nanorods is 1 to 20 mg / mL; and / or the average diameter of the Bi2S3 nanorods is 60-100 nm and the length is 500-800 nm; the V2CT x The average size of the nanosheets is 2-3 μm; and / or the first solvent is selected from at least one of deionized water, ethylene glycol and ethanol; And / or the second solvent is selected from at least one of deionized water, methanol and ethanol.

3. The preparation method according to any one of claims 1 to 2, characterized in that: The volume ratio of the hydrofluoric acid to the hydrochloric acid is (1-3):1; and / or the ratio of the total amount of the hydrofluoric acid and the hydrochloric acid to the V2AlC is (10-40) mL:1 g; and / or the stirring etching condition is stirring at 30-40°C for 12-36 hours, and then stirring at 45-55°C for 36-60 hours; and / or the molar ratio of the sodium sulfide nonahydrate to the bismuth nitrate is 2:(0.5-1.5); And / or the conditions of the first hydrothermal reaction and the second hydrothermal reaction are independently: reacting at 100-200° C. for 10-30 hours.

4. Bi2S3-V2CT prepared by the preparation method according to any one of claims 1 to 3 x Heterojunction materials.

5. A gas sensor, characterized in that: The gas-sensitive layer comprises a gas-sensitive material, wherein the gas-sensitive material comprises Bi2S3-V2CT prepared by the preparation method according to any one of claims 1 to 3. x Heterojunction material or Bi2S3 / V2CT as claimed in claim 4 x Heterojunction materials.

6. The gas sensor according to claim 5, characterized in that The gas sensor further comprises a substrate and interdigital electrodes, wherein the interdigital electrodes are arranged on at least one side of the substrate, and the gas sensitive layer is arranged on a surface of the interdigital electrodes which is away from the substrate.

7. The gas sensor according to claim 6, characterized in that The substrate is selected from one or more of silicon, polymer, ceramic and sapphire substrates; and / or the distance between the positive and negative electrodes of the interdigitated electrodes is 200 to 900 μm; And / or the number of the interdigital electrodes is one or more. When the number of the interdigital electrodes is plural, the interval between two adjacent interdigital electrodes is 50-500 μm.

8. The method for preparing a gas sensor according to any one of claims 5 to 7, characterized in that: The steps include: Step 1, providing interdigital electrodes on a substrate; Step 2: Prepare the gas-sensitive material into a gas-sensitive layer dispersion, apply it onto the surface of the interdigital electrode away from the substrate, dry it to form a gas-sensitive layer, and prepare the gas sensor.

9. A gas sensing device, characterized in that: The invention comprises the gas sensor according to any one of claims 5 to 7 or the gas sensor prepared by the preparation method according to claim 8.

10. Bi2S3-V2CT prepared by the preparation method according to any one of claims 1 to 3 x Heterojunction material, Bi2S3 / V2CT as claimed in claim 4 x Application of a heterojunction material, a gas sensor according to any one of claims 5 to 7, a gas sensor prepared by the preparation method according to claim 8, or a gas sensing device according to claim 9 in nitrogen dioxide sensing.